Ensuring the rule of law by the court system in Vietnam after the ratification of the 2013 constitution: challenges and prospects 1 - To, Van Hoa (Đại học Quốc Gia Hà Nội, 2020)
The paper emphasizes constructively the role of courts in ensuring the rule of law by pointing out challenges and prospects courts are facing in the current context. After the birth of the Constitution 2013, courts have obtained more favourable conditions to play such role as shown in the principle on control of state powers, court’s mandate on protection of justice, the principle of respect for human rights, and the birth of case laws. These elements not only set forth prospects, but they are also challenges to the judicial and legal system for more effective protection of the rule of law.